Ag₂S–Ag Nanocomposites: A Bottom-Up Approach to Enhance Thermoelectric Power Factor at Near Room Temperature - Anish Kumar (International Journal of Electro-Mechanics and Material Behaviour, 2026)
The intrinsic ductility, low toxicity, and naturally occurring abundance of silver sulphide (Ag₂S) have made it a potential thermoelectric material in recent years. However, high electrical resistance severely limits its practical application. Here, we present a thorough analysis of how metallic Ag nanoinclusions affect the structural, electrical, and thermoelectric characteristics of Ag₂S nanocomposites made using a simple bottom-up polyol approach. (Ag₂S)₁₋ₓAgₓ nanocomposites with an Ag content ranging from 0 to 26.1% were produced by controlling the inclusion of Ag nanoparticles by adjusting the proportion of sulphur precursor. X-ray diffraction with Rietveld refinement, FESEM-EDX, and X-ray photoelectron spectroscopy are used in structural and phase investigations to confirm the coexistence of monoclinic α-Ag₂S and face-centered cubic Ag phases with uniform interfacial distribution.A semiconductor-to-metal transition controlled by percolative charge transport through Ag-rich grain boundaries is observed together with a consistent decrease in resistivity with increasing Ag concentration, according to electrical transport measurements. Interestingly, for modest amounts of Ag nanoinclusion, improved Seebeck coefficients close to room temperature are seen, which is explained by low-energy charge carrier filtering at semiconductor–metal contacts. The composite comprising approximately 20.1% Ag achieves a maximum figure of merit ZT = 0.0029 at 325 K and an optimised thermoelectric power factor of 19.53 μW·m⁻¹·K⁻². These findings show that Ag nanoinclusion offers a practical means to separate electrical conductivity and Seebeck coefficient in Ag₂S, creating a feasible route toward mechanically sound, ecologically safe thermoelectric materials that function close to ambient temperature.
Keywords: Ag nano inclusions; Ag₂S nanocomposites; Seebeck coefficient; carrier filtering; electrical transport; power factor; thermoelectric materials